Taking into Account Individual Peculiarities of Junior Schoolchildren when Choosing the Methods of Upbringing in Out-of-Class Upbringing Work - Nataliya Kazakova (Pedagogical Discourse, 2013)
The necessity of working out new approaches as for the use of methods of upbringing in out-of-class time is stipulated by the number of factors: substantial changes are taking place in methodological base of the educational thery and methods of education; to replace the society’s demands the paradigm of humanistic, personaly-oriented education had come; theoretical, methodical and practical set of psychologic and pedagogical diagnostics is getting richer, that allows to master diagnostical instruments of research of effectiveness of teaching methods use. All these circumstances need theoretical grounding of conditions of use ofprimary school puils  teaching methods in their out-of-class activity. The account of individual peculiarities of junior pupils when choosinf the methods of upbringing in out-of-class upbringing work is one of them.